Using UML and OCL as languages to define DEVS atomic models - Blas, María Julia; Gonnet, Silvio (2020 Winter Simulation Conference, 2020)
This paper presents a work-in-progress intended to define the foundations for building a representation of DEVS using conceptual modeling languages from information system engineering. We use UML and OCL languages to define a metamodel that conceptualizes atomic DEVS models. Such a representation enhances the DEVS modeling activity providing atomic model definitions as instances of the metamodel developed.
Keywords: OCL; UML; DEVS atomic models